An evaluation of process-parameter and part-geometry effects on the quality of filling in micro-injection moulding - Attia, Usama M.; Alcock, Jeffrey R. (Springer Science Business Media, 2009)
This paper addresses the use of micro-injection moulding for the fabrication of polymeric parts with microfeatures. Five separate parts with different micro- feature designs are moulded of Polymethylmethacrylate. The design-of-experiments approach is applied to correlate the quality of the parts to the processing parameters. Five processing parameters are investigated using a screening half- factorial experimentation plan to determine their possible effect on the filling quality of the moulded parts. The part mass is used as an output parameter to reflect the filling of the parts. The experiments showed that the holding pressure is the most significant processing parameter for all the different shapes. In addition, the experiments showed that the geometry of the parts plays a role in determining the significant processing parameters. For a more complex part, injection speed and mould temperature became statistically significant. A desirability function approach was successfully used to improve the filling quality of each part.
Keywords: Micro-injection moulding; Design of experiments; Geometry; Processing parameters; Quality control